Resin dentin bond´s resistance using three adhesive systems at different application times. Study in vitro - Arquíñego Garay, Ketty Amelia (2019)
Objective. To evaluate the dentin-resin bond´s resistance (DRBR) of the adhesives Optibond FL (OFL), Adper Single Bond 2 (ASB2) and Single Bond Universal (SBU) with its self-engraving possibility, in three different times of application. Methods. Experimental, comparative and crossectional in vitro study. We used nine human molars, obtaining 135 specimens of 1 mm2 approximately, forming nine study groups of 15 specimens for each group. The DRBR was measured through the Microtunsion test at a tensile force with an acceleration of 0.5mm/min until a fracture.The contrast of difference hypotheses was performed using the one-factor ANOVA test and Tukey's multiple comparisons, both at a confidence level of 95%. Results. After 10 seconds, significant differences were found between the OFL adhesive systems (25.78 ± 5.98 MPa) vs ASB2 (from 14.02 ± 3.06 MPa) at p<0.001, as well as between OFL vs SBU (14.36 ± 4.69 MPa) with p<0.001. At 20 seconds, between OFL (34.37 ± 6.03 MPa) and ASB2 (16.33 ± 3.02 MPa) at level p<0.001, as well as between OFL and SBU (19.44 ± 5.98 MPa) with p<0.001. After 30 seconds, the same differences were found between OFL (37.6 ± 11.93 MPa) and ASB2 (16.62 ± 1.81 MPa) at p<0.001, as well as between OFL and SBU (23.56) ± 7.3 MPa) with p<0.001. Conclusions. OFL presented greater DRBR compared to ASB2 and SBU in the three rubs; between ASB2 and SBU rubbing 10 s no difference was found, rubbing 20 s and 30 s SBU presented higher DRBR. In all three groups there was a significant increase in DRBR between 10 and 30 seconds.